The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1161/circgenetics.116.001533
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in the SLC8A1 Calcium Signaling Pathway Is Associated With Susceptibility to Kawasaki Disease and Coronary Artery Abnormalities

Abstract: Background— Kawasaki disease (KD) is an acute pediatric vasculitis in which host genetics influence both susceptibility to KD and the formation of coronary artery aneurysms. Variants discovered by genome-wide association studies and linkage studies only partially explain the influence of genetics on KD susceptibility. Methods and Results— To search for additional functional genetic variation, we performed pathway and gene stability analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 35 publications
(46 reference statements)
0
37
1
Order By: Relevance
“…231,232 Cyclosporine is a specific inhibitor of calcineurin, and a protocol for its administration and monitoring has been used successfully in a small number of highly resistant patients.…”
Section: Cyclosporinementioning
confidence: 99%
See 1 more Smart Citation
“…231,232 Cyclosporine is a specific inhibitor of calcineurin, and a protocol for its administration and monitoring has been used successfully in a small number of highly resistant patients.…”
Section: Cyclosporinementioning
confidence: 99%
“…230 Second, genetic studies in children of Japanese or European descent have implicated activation of the NFAT-calcineurin calcium signaling pathway as a contributor to both disease susceptibility and coronary artery aneurysm formation. 231,232 Cyclosporine is a specific inhibitor of calcineurin, and a protocol for its administration and monitoring has been used successfully in a small number of highly resistant patients. 216 Dosing is provided in Table 6; levels are monitored to arrive at the appropriate dose but not monitored thereafter.…”
Section: Cyclosporinementioning
confidence: 99%
“…Although the serum levels of CaN in KD patients with CALs had no significant difference from those in KD patients without CALs due to limited sample size, the serum levels of NFAT1 in KD patients with CALs were lower significantly than those in KD patients without CALs at afebrile stage, which suggest that NFAT1 levels decline much rapidly after the standard IVIG treatment in the KD patients with CALs than those without CALs. A recent study has confirmed that homozygous KD patients for the SLC8A1 A (risk) allele of rs13017968 were more likely to develop coronary artery aneurysms [17], which suggested the activation and importance of calcium signaling pathway in KD patients with CALs. These findings seemed to be consistent with our study, suggesting the availability of using CNIs in KD with CALs.…”
Section: Discussionmentioning
confidence: 91%
“…By using the CNIs to block the NFAT translocation to the nucleus, the inflammation of KD at acute stage could be relieved. The CaN-NFAT signal pathway as a contributor had been found to be associated with KD susceptibility and CALs formation, growing out of 3 functional single nucleotide polymorphisms (SNPs) in ITPKC, CASP3 and SLC8A1(solute carrier family 8, member 1, a sodium/ calcium exchanger encoding NCX1) gene [11,12,17].…”
Section: Discussionmentioning
confidence: 99%
“…Variants in calcium signaling pathway genes, such as solute carrier family 8, member 1 (SLC8A1), which influence KD susceptibility were discovered using pathway analysis followed by gene stability selection in the dataset from a KD genome wide association study (GWAS). 3 Because genetic variants in these calcium signaling pathway genes have been associated with abnormalities of myocardial repolarization [4][5][6] and QT intervals in other conditions, we performed a pilot study to analyze the electrocardiogram (ECG) in KD subjects carrying the validated risk alleles in SLC8A1. 4,7 In the pilot study, we noted bifid T waves in the limb leads in a subset of subjects.…”
Section: Introductionmentioning
confidence: 99%